PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE BERBANTUAN APLIKASI KAHOOT TERHADAP PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA SEKOLAH DASAR - Roka, Rania; Nurmahanani, Indah; Mulyani , Srie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Writing is a crucial skill that students must possess, including the ability to write descriptive texts. However, the reality in the field indicates that elementary school students do not yet have the expected skill in writing descriptive texts. Therefore, to enhance students' skills in writing descriptive texts, innovations in teaching are necessary, one of which is using the Cooperative Learning model of Picture and Picture aided by the Kahoot! application. This study aims to assess elementary school students' skills in writing descriptive texts and to determine the impact of the Cooperative Learning model of Picture and Picture aided by the Kahoot! application on improving these skills. The research method employed was pre-experimental research with a one-group pretest-posttest design. The sample was selected using purposive sampling, consisting of 22 grade IV students from an elementary school in Karawang Regency. The instruments used in this study were essay tests, as well as observation sheets for teachers and students. The results of the study indicated a 40.3% improvement in students' skills in writing descriptive texts. Furthermore, there was a noticeable difference in students' skills in writing descriptive texts before and after applying the Cooperative Learning model of Picture and Picture aided by the Kahoot! application.